Hubungan Antara Keseimbangan Terhadap Keterampilan Sepak Sila Dalam Permainan Sepak Takraw Pada Siswa Ekstrakurikuler Sma Negeri 2 Bengkulu Selatan) - Effendi, Erlis Surya; Perdima, Feby Elra; Martiani, Martiani (Journal Of Dehasen Educational Review, 2024)
This study aims to determine the relationship between balance and sepaksila skills in takraw games for extracurricular students of SMAN 2 Bengkulu Selatan. correlation or correlational research is research that seeks to determine whether there is a relationship between 2 or more variables. the independent variable is balance with the dependent variable, sepaksila skills. The type of sempel in this study used the total sampling technique. The sempel is all SMA Negeri 2 South Bengkulu takraw players totaling 11 people. The instruments used in this study were balance tests and sepaksila skills.the results of the balance test (X) score Lhitung 0.123 with n = 11 while L tab at a significant level of 0.05 obtained 0.258. Because Lcount is smaller than Ltab, it is concluded that the score obtained from the balance is normally distributed. And the data above the test results of sepaksila skills (Y) score Lhitung 0.121 with n = 11 while Ltab at a significant level of 0.05 obtained 0.258. so Lhitung is smaller than Ltab, it can be concluded that the scores obtained from sepaksila skills are normally distributed